Pengaruh Human Capital Dan Entrepreneurial Orientation Terhadap Business Competitiveness Dan Market Orientation Sebagai Variabel Moderator (Studi Kasus Umkm Di Kota Sukabumi) - Rosa Rosdiana; Bambang Somantri (ITB AAS Indonesia Surakarta, 2024)
This research is based on the problems found regarding the company's competitiveness variable, namely that there is very tight competition due to the large number of MSMEs circulating in the city of Sukabumi. The aim of this research is to analyze the influence of Human Capital, Entrepreneurial Orientation, and Market Orientation as moderator variables on Business Competitiveness, by using a case study of MSMEs in the city of Sukabumi. This research method uses a survey method by distributing questionnaires and using 100 respondents, while the instrument quality testing technique is validity testing and reliability testing. Classic assumption testing techniques refer to the normality test, multicollinearity test, heteroscedasticity test, and auto correlation test. Hypothesis testing uses multiple linear regression analysis, determination test, partial t test, simultaneous f test, and Moderated Regression Analysis test. Based on testing the results of this research, the Human Capital variable has a significant effect on Business Competitiveness, the Entrepreneurial Orientation variable has a significant effect on Business, the Human Capital variable has no significant effect on Business Competitiveness which is moderated by the Market Orientation variable, and the Entrepreneurial Orientation variable has a significant effect on Business Competitiveness which is moderated by the Market Orientation variable.